# Solve for a -5(1-5a)+5(-8a-2)=-4a-8a -5(1-5a)+5(-8a-2)=-4a-8a
Simplify -5(1-5a)+5(-8a-2).
Simplify each term.
Apply the distributive property.
-5⋅1-5(-5a)+5(-8a-2)=-4a-8a
Multiply -5 by 1.
-5-5(-5a)+5(-8a-2)=-4a-8a
Multiply -5 by -5.
-5+25a+5(-8a-2)=-4a-8a
Apply the distributive property.
-5+25a+5(-8a)+5⋅-2=-4a-8a
Multiply -8 by 5.
-5+25a-40a+5⋅-2=-4a-8a
Multiply 5 by -2.
-5+25a-40a-10=-4a-8a
-5+25a-40a-10=-4a-8a
Simplify by adding terms.
Subtract 10 from -5.
25a-40a-15=-4a-8a
Subtract 40a from 25a.
-15a-15=-4a-8a
-15a-15=-4a-8a
-15a-15=-4a-8a
Subtract 8a from -4a.
-15a-15=-12a
Move all terms containing a to the left side of the equation.
Add 12a to both sides of the equation.
-15a-15+12a=0
Add -15a and 12a.
-3a-15=0
-3a-15=0
Add 15 to both sides of the equation.
-3a=15
Divide each term by -3 and simplify.
Divide each term in -3a=15 by -3.
-3a-3=15-3
Cancel the common factor of -3.
Cancel the common factor.
-3a-3=15-3
Divide a by 1.
a=15-3
a=15-3
Divide 15 by -3.
a=-5
a=-5
Solve for a -5(1-5a)+5(-8a-2)=-4a-8a

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top